2020
DOI: 10.1021/acsabm.0c00039
|View full text |Cite
|
Sign up to set email alerts
|

Polymerized Hemoglobin With Increased Molecular Size Reduces Toxicity in Healthy Guinea Pigs

Abstract: Hemoglobin (Hb)-based oxygen (O2) carriers (HBOCs) have been developed as an alternative to red blood cells (RBCs) for use in transfusion medicine. HBOCs have many benefits over RBCs; however, previous generations of HBOCs failed in clinical trials due to unanticipated cardiotoxicity. These problems likely originated from vasoconstriction, hypertension, oxidative stress, and the presence of low-molecular-weight (MW) Hb species in the HBOC formulation. Therefore, the objective of this study is to compare the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…A more recently developed large molecular weight polymerized human Hb (PolyhHb), which preserves microvascular hemodynamics and effectively restores O 2 delivery during HS alone, could be a promising resuscitation alternative to current resuscitation strategies from HS after TBI 21 . Previously, our research group evaluated the efficacy of this next generation PolyhHb in different animal models 22 , but no studies of these therapies on resuscitation from HS after TBI have been completed until now. This study evaluated the efficacy of large molecular weight PolyhHb to restore blood pressure after resuscitation from hemorrhagic shock post-TBI compared to lactated Ringer’s solution (LR, electrolyte solution used to restore the loss of blood volume), and fresh whole blood (Blood, autologous blood drawn during hemorrhage).…”
Section: Introductionmentioning
confidence: 99%
“…A more recently developed large molecular weight polymerized human Hb (PolyhHb), which preserves microvascular hemodynamics and effectively restores O 2 delivery during HS alone, could be a promising resuscitation alternative to current resuscitation strategies from HS after TBI 21 . Previously, our research group evaluated the efficacy of this next generation PolyhHb in different animal models 22 , but no studies of these therapies on resuscitation from HS after TBI have been completed until now. This study evaluated the efficacy of large molecular weight PolyhHb to restore blood pressure after resuscitation from hemorrhagic shock post-TBI compared to lactated Ringer’s solution (LR, electrolyte solution used to restore the loss of blood volume), and fresh whole blood (Blood, autologous blood drawn during hemorrhage).…”
Section: Introductionmentioning
confidence: 99%
“…The PolyHb used in this study was shown to be vasoactive in other species (guinea pigs), and reduction of the LMW PolyHb species via diafiltration reduced the vasoactivity. 10 By targeting the LMW Hb species directly with apoHb-Hp and Hp, there is no need to balance a pressor response.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should examine the relative effectiveness of the apoHb-Hp complex after transfusion of larger volumes of PolyHb and explore the long-term consequences of the apoHb-Hp complex in other manifestations of acellular Hb toxicity beyond vasoactivity. Unfortunately, the results of this study cannot be directly extrapolated to humans, and additional preclinical studies in other species with different vasoactive mechanisms should be explored, including guinea pigs 10 and lambs, 48 to supplement the current investigation of the microcirculation in the window chamber model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PolybHb preserves microvascular hemodynamics, does not induce vasoconstriction, and effectively restores O 2 delivery and utilization by tissues 11 . However, even after filtration, the solution still possesses a small amount of highly vasoactive low molecular weight material, and as such, before clinical trials can proceed with high MW PolybHb formulations, new studies are necessary to characterize the safety and efficacy of PolybHb 12 . The clinical trial failures with previous HBOCs suggest that preclinical animal testing may not have been sufficiently predictive of safety in humans.…”
Section: Introductionmentioning
confidence: 99%